Development of KoGOPEQ Interactive Learning Videos to Improve the Independent and Honest Characters of Students - Putu Pradnyadewi; IM Ardana; Gede Suweken (International Journal of Education, Management, and Technology, 2026)
Although the integration of character education and technology in mathematics learning has received increasing attention in prior studies, research specifically examining the combined use of interactive video platforms with the Teacher–Parent–Student Collaboration (KoGOPEQ) model to simultaneously enhance independent and honest character alongside cognitive understanding remains limited. This study aims to design, implement, and evaluate the effectiveness of an interactive learning video based on the KoGOPEQ model in improving the independent and honest character of fourth-grade elementary students during fraction lessons. Employing a research and development (R&D) approach, the study adopts the Plomp and Nieveen model—comprising preliminary research, prototyping, and assessment phases—and involves 48 fourth-grade students as primary respondents. Data were collected using expert validation sheets, practicality questionnaires for teachers and students, character observation sheets, and pretest–posttest instruments, and were analyzed using descriptive qualitative and quantitative techniques, including gain score calculations. The findings indicate that the developed interactive video is highly valid (score = 4.50), very practical (83.58%), and effective, with gain scores of 0.80 for independence and 0.77 for honesty, as well as a substantial increase in mathematics learning outcomes from an average of 41.78 to 72.18. These results contribute to the theoretical development of multimedia learning within collaborative school–family frameworks and expand understanding of how digital tools can holistically support students’ character and cognitive growth. The study concludes that KoGOPEQ-oriented interactive learning videos play a crucial role in bridging the gap between academic difficulty and character building, and recommends that educators and parents actively adopt this collaborative medium to support student development. The implications include theoretical contributions to the literature on interactive instructional design and practical recommendations for educational institutions seeking to strengthen the Pancasila student profile. Furthermore, this study highlights opportunities for future research on extending the model to other character dimensions and subject areas.